The orf162b Sequence of Rhodobacter capsulatus Encodes a Protein Required for Optimal Levels of Photosynthetic Pigment-Protein Complexes - Aklujkar, Muktak (American Society for Microbiology, 2000)
The orf162b sequence, the second open reading frame 3′ of the reaction center (RC) H protein gene puhA in the Rhodobacter capsulatus photosynthesis gene cluster, is shown to be transcribed from a promoter located 5′ of puhA. A nonpolar mutation of orf162b was generated by replacing most of the coding region with an antibiotic resistance cartridge. Although the mutant strain initiated rapid photosynthetic growth, growth slowed progressively and cultures often entered a pseudostationary phase. The amounts of the RC and light harvesting complex I (LHI) in cells obtained from such photosynthetic cultures were abnormally low, but these deficiencies were less severe when the mutant was grown to a pseudostationary phase induced by low aeration in the absence of illumination. The orf162b mutation did not significantly affect the expression of a pufB::lacZ translationally in-frame gene fusion under the control of the puf promoter, indicating normal transcription and translation of RC and LHI genes. Spontaneous secondary mutations in the strain with the orf162b disruption resulted in a bypass of the photosynthetic growth retardation and reduced the level of light harvesting complex II. These results and the presence of sequences similar to orf162b in other species indicate that the Orf162b protein is required for normal levels of the photosynthetic apparatus in purple photosynthetic bacteria.